Perubahan Nilai Gizi dan Alergenisitas Produk Olahan Intermediat Surimi dan Otak-Otak Ikan Tenggiri Siap Santap - Vina Giovani; Nurheni Sri Palupi; Dian Herawati; Saraswati (Jurnal Teknologi dan Industri Pangan, 2023)
Fish is one of the nine major food allergens. Avoiding consumption of fish is a common preventive measure to mitigate fish allergies. On the other hand, food processing may potentially alter the allergenicity of fish, and thus, it is important to identify the most effective fish processing methods that can reduce its allergenicity. This research aimed to characterize the nutritional value, intensity of allergens, and allergenicity from the processing of tenggiri fish processing to produce surimi as intermediate food and ready to eat (RTE) otak-otak. The processing steps consisted of washing and adding cryoprotectant during surimi processing, and using deep and air frying methods in RTE otak-otak processing. Changes in the nutritional value and intensity of allergens of fish meat and its processed products were measured using proximate analysis and SDS-PAGE electrophoresis, respectively. The alterations in the allergenicity were investigated using immunoblotting and ELISA. The results revealed changes in the nutritional value due to the processing. Surimi production successfully removed a protein band of 10-–13 kDa, which is suspected to be an allergen. Additionally, both deep and air frying methods effectively removed allergenic proteins with molecular weights above 100 kDa. Immunoblotting assay showed the allergen only appeared in fish meat absent in all of the processed products. The allergenicity rates of surimi and otak-otak was reduced by 90.78 and 98.68%, respectively, as compared to the fish meat. In conclusion, the nutritional value of air-fried otak-otak is superior while the allergenicity is lower than the deep-fried ones. Therefore, air frying processing method for tenggiri fish can be potently used to produce hypoallergenic fish products.